Analisis Faktor Yang Mempengaruhi Produktivitas Tenaga Kerja pada Proyek Pembangunan Perumahan Opra City Gresik Jawa Timur - Bagaskara, Jordan Setyo; Triana, Masca Indra (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Labor productivity is one of the main elements in determining the success of a construction project. The purpose of this research was to find out what factors influence labor productivity. This research was conducted at the Opra City Gresik Housing Development Project. The method used to find the relationship between productivity and factors that influence productivity is the Productivity Rating method, multiple linear regression analysis method, t test, F test (Anova) and coefficient of determination using statistical software, namely SPSS version 23. There are other analysis methods that are used. used are the validity test, reliability test and normality test used in testing the questionnaire. The level of worker productivity is 81.80%. This can be said to be quite satisfactory, because the Worker Utility Factor is more than 50%. There are seven factors that are most dominant in influencing productivity, namely uncertain weather, lack of material availability, damaged equipment, education level, age, worker motivation and quality of supervision.